Darwin's finches habitually anoint their feathers with leaves of the endemic tree Psidium galapageium during the non‐breeding season. (31st March 2021) - Tebbich, Sabine; Schwemhofer, Timo; Fischer, Barbara; Pike, Courtney
Abstract: Birds host a wide range of ectoparasites and have developed behavioural strategies to combat them, such as preening, dust bathing and water bathing. In addition, a wide range of avian taxa anoint their feathers with insects or plants that have pharmaceutical properties, though most observations on anointing are anecdotal. Darwin's finches preen with leaves of an endemic tree ( Psidium galapageium ) and a previous laboratory study has shown that this plant has compounds that repel both mosquitoes and the invasive parasitic fly Philornis downsi, whose larvae suck blood from nestlings and incubating females and cause high nestling mortality. In the current study, we tested the hypothesis that preening with P . galapageium leaves serves to repel these parasites with an indirect approach. Mosquitoes and P . downsi affect their hosts mainly during the bird breeding season and P . downsi only affects breeding females, but not adult males. To test our hypothesis, we gathered quantitative data on leaf‐preening behaviour in Darwin's finches during their breeding and non‐breeding season and also investigated the influence of time of day and humidity, as humid conditions facilitate the release of volatile organic compounds. Contrary to our predictions, anointing occurred significantly more often during the non‐breeding season when mosquito and P . downsi numbers are lower. Four Darwin's finch species anointed their feathers habitually, and during the non‐breeding season, 56% of all preening events were with leaves. We found no effect of sex, but preening with leaves occurred predominately in the morning when leaves were wet. Our study is the first to provide quantitative data on anointing behaviour in birds and the high percentage of preening with leaves in the non‐breeding season suggests that the behaviour has an adaptive value. However, further studies are needed to test whether it reduces the negative impact of parasites other than mosquitoes and P . downsi . Abstract : Our study revealed that four species of Darwin's finches habitually anoint their feathers with leaves of the endemic tree Psidium galapageium, which contain volatiles with anti‐parasitic properties. We observed anointing most frequently in the morning when leaves are still wet and probably omit more volatiles. During the non‐breeding season 56% of all preening events included the use of leaves, suggesting that this behaviour has adaptive value. However, further studies are needed to establish if it serves to repel parasites.